2015
DOI: 10.1111/juaf.12173
|View full text |Cite
|
Sign up to set email alerts
|

If Detroit Is Dead, Some Things Need to Be Said at the Funeral

Abstract: A growing literature has long proclaimed the city of Detroit to be “dead.” Of course cities, unlike sentient beings, do not actually die even if they dramatically lose industry and population and the local government its ability to meet basic needs. How their continuing crisis is addressed depends on how competing interests are able to tell their story. This essay evaluates the most significant of these competing and complementary stories and evaluates state‐appointed Emergency Financial Manager Kevyn Orr's pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In contrast to the opinion of some urban planners from the late twentieth century that Detroit could hardly ever be reconstructed (Eisinger 2003), the more recent optimistic viewpoint reminded that, in contrast to real death, city doesn't physically disappear, making revitalization of Detroit eventually a real possibility (Tabb 2015). Examples of former industrial cities of Chicago or Pittsburgh already demonstrated that death of industry didn't necessarily mean inability for a different city to evolve, although this surely depended not only on innovative strategies, but also on power relations in a city in question, political will and entrepreneurialism of the local government, and effective and collaborative framework for successful implementation.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In contrast to the opinion of some urban planners from the late twentieth century that Detroit could hardly ever be reconstructed (Eisinger 2003), the more recent optimistic viewpoint reminded that, in contrast to real death, city doesn't physically disappear, making revitalization of Detroit eventually a real possibility (Tabb 2015). Examples of former industrial cities of Chicago or Pittsburgh already demonstrated that death of industry didn't necessarily mean inability for a different city to evolve, although this surely depended not only on innovative strategies, but also on power relations in a city in question, political will and entrepreneurialism of the local government, and effective and collaborative framework for successful implementation.…”
Section: Discussionmentioning
confidence: 85%
“…Some of Michigan's politicians blamed this legislation for pushing Detroit out of world auto markets (Tabb 2015). Nevertheless, the most logical explanation of the city's dramatic decline is that local elected officials were not willing to make hard choices for addressing changing circumstances.…”
Section: Background Of the Crisis In Detroit And Analysis Of The Follmentioning
confidence: 99%
See 2 more Smart Citations
“…The media narrative in particular has changed since the bankruptcy from generally negative, to mixed, to the quite positive stories appearing in 2015. A variety of sources, ranging from the New York Times, to the Huffington Post, to social media blogs, highlight several themes: the increasing attractiveness of Detroit to young people, particularly entrepreneurs and millennials, because of the low costs of housing, retail and warehouse space, and a market that is wanting for local products and amenities of all types [5,19,20]; the burgeoning artistic scene, fueled by low prices for artist housing and workplaces [1]; increasingly vibrant restaurant, nightlife and theatre options [21]; the attractiveness to tourists of these trends plus the continuing opportunity to tour and photograph "ruins" [1]; increasing levels of foreign investment, particularly from China [4,22]; a gritty, "can-do," and underdog attitude among Detroit residents [22]; the talent pool produced by local universities [24]. While many of these stories do mention the bankruptcy, the burned out buildings, the large swaths of vacant land, the crime, and the poverty, they are increasingly being presented as the back-drop for regeneration -"yes, this is still America's most dangerous city, but it is far from downtrodden" [3].…”
Section: Transition In Narratives: From the Cass Corridor To Midtownmentioning
confidence: 99%